Social media travel influencers' attributes and tourists' travel intention: the role of source credibility / Mohammad Faisal and Devendra Kumar Dhusia - Faisal, Mohammad; Dhusia, Devendra Kumar (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
Social media influencer marketing is redefining the marketing strategies and has become a powerful tool therein. Social media travel influencers are common people who have social media channels or pages through which they shape their followers' perceptions. This research study attempts to analyse the credibility traits of social media travel influencers and the travel intent of tourists in Delhi and the National Capital Region. A structured questionnaire was designed and shared online to collect data. A total of 166 responses were received and only 100 are valid. This study utilised quota sampling for the selection of the sample, and data is analysed with the help of SmartPLS3 for measurement and structural model evaluation. The results disclose that expertise, intimate self-disclosures (ISDs), and trustworthiness have a significant effect on influencers' credibility, while credibility and intimate self-disclosures (ISDs) have a significant direct effect on tourists' travel intention. Moreover, trustworthiness also showed a significant indirect effect on tourists' travel intention. These findings establish the importance of credibility traits and the mediating role of credibility between the traits and tourists' travel intention. Marketers should consider the influencer's expertise and credibility to select a travel influencer whose content is perceived as intimate and credible.